Comparison of drying behavior and product quality of coconut chips treated with different osmotic agents. (1st June 2022) - Pravitha, M.; Manikantan, M.R.; Ajesh Kumar, V.; Shameena Beegum, P.P.; Pandiselvam, R.
Abstract: The feasibility of using non-conventional osmotic agents such as coconut sugar, and jaggery in coconut chips production was evaluated, and compared with sucrose treated chips in terms of quality and sensory attributes. Samples were processed at the identical condition of 0.60 mm slice thickness, 45 o Brix solution concentration, and 65 °C drying temperature. Osmotic dehydration ability of different osmotic agents on coconut slices was found to be comparable in terms of water loss and solute gain. Pretreatment significantly enhances mass transfer rate of water during convective drying. However, sucrose treated samples shown slightly higher effective diffusivity values during both osmotic dehydration and hot air drying due to the inherent nature of solution. Introduction of new osmotic agents was positively reflected in the sensory attributes. Other important quality indices like rehydration ratio, solute gain, textural parameters and hygroscopicity also came under an acceptable range for all samples. Thin-layer drying behavior of slices was analyzed with six widely used drying models. According to the model fittings, the drying behavior of sucrose and jaggery-treated slices can be well described by the modified Henderson and Pabis equation, and the logarithmic equation was best suited to coconut sugar-based chip samples. Highlights: Jaggery and coconut sugar based coconut chips exhibited higher sensory score. Coconut chips with new osmotic agents shown higher antioxidant activity. Osmotic dehydration ability of novel osmotic agents is comparable with conventional ones.